Kin networks and opportunities for reproductive cooperation and conflict among hunter–gatherers. (16th January 2023) - Hackman, Joseph; Kramer, Karen L.
Abstract : Little is known about the potential for reproductive conflict among hunter–gatherer populations, who are characterized by bilateral kinship ties, flexible residential mobility, and high offspring mortality. To assess the potential for reproductive conflict, we use longitudinal residence and reproductive history data for two bands of South American foragers. Using multilevel logistic regressions ( N = 44 women, N = 712 person years), we examine how yearly measures of (i) camp composition, (ii) distribution of female kin and (iii) a woman's position in a female kinship network impact the likelihood of giving birth or experiencing a child's death. We compare conflict models to a demographic model that accounts for the proportion of women giving birth in a given year. Contrary to conflict models, results show that the odds of giving birth increase with the presence of highly related women. However, the odds of experiencing an offspring death are insensitive to the presence of coresident women. Network measures of closeness and centrality in the female kin network also show no significant effect on reproductive outcomes. Furthermore, chances of both births and deaths increase in years when proportionally more women are giving birth. We argue that demographic stochasticity relating to ecological conditions best predicts reproductive outcomes for women. This article is part of the theme issue 'Cooperation among women: evolutionary and cross-cultural perspectives'.